Stimulation of the soluble guanylate cyclase (sGC) inhibits fibrosis by blocking non-canonical TGFβ signalling. Issue 7 (23rd February 2014) - Beyer, Christian; Zenzmaier, Christoph; Palumbo-Zerr, Katrin; Mancuso, Rossella; Distler, Alfiya; Dees, Clara; Zerr, Pawel; Huang, Jingang; Maier, Christiane; Pachowsky, Milena L; Friebe, Andreas; Sandner, Peter; et al.
Abstract : Objectives: We have previously described the antifibrotic role of the soluble guanylate cyclase (sGC). The mode of action, however, remained elusive. In the present study, we describe a novel link between sGC signalling and transforming growth factor β (TGFβ) signalling that mediates the antifibrotic effects of the sGC. Methods: Human fibroblasts and murine sGC knockout fibroblasts were treated with the sGC stimulator BAY 41-2272 or the stable cyclic guanosine monophosphate (cGMP) analogue 8-Bromo-cGMP and stimulated with TGFβ. sGC knockout fibroblasts were isolated from sGCI fl/fl mice, and recombination was induced by Cre-adenovirus. In vivo, we studied the antifibrotic effects of BAY 41-2272 in mice overexpressing a constitutively active TGF-β1 receptor. Results: sGC stimulation inhibited TGFβ-dependent fibroblast activation and collagen release. sGC knockout fibroblasts confirmed that the sGC is essential for the antifibrotic effects of BAY 41-2272. Furthermore, 8-Bromo-cGMP reduced TGFβ-dependent collagen release. While nuclear p-SMAD2 and 3 levels, SMAD reporter activity and transcription of classical TGFβ target genes remained unchanged, sGC stimulation blocked the phosphorylation of ERK. In vivo, sGC stimulation inhibited TGFβ-driven dermal fibrosis but did not change p-SMAD2 and 3 levels and TGFβ target gene expression, confirming that non-canonical TGFβ pathways mediate the antifibrotic sGC activity. Conclusions: We elucidated the antifibrotic mode of action of the sGC that increases cGMP levels, blocks non-canonical TGFβ signalling and inhibits experimental fibrosis. Since sGC stimulators have shown excellent efficacy and tolerability in phase 3 clinical trials for pulmonary arterial hypertension, they may be further developed for the simultaneous treatment of fibrosis and vascular disease in systemic sclerosis.